Between Urgency and Inertia: Spatial Planning in Transformation - Bruns, Antje (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
The urgency of fundamental socio-ecological transformation is scientifically uncontested, yet institutions – including spatial planning – predominantly act sluggishly, reinforcing existing paths of unsustainability. Despite normative orientations such as the sustainability principle within the German spatial planning law, planning practice has so far struggled to enable and accelerate socio-ecological transformations towards sustainability. This comment highlights the tensions between planning’s ambitions and its realities, emphasizes the importance of exnovation and unlearning as key dimensions of socio-ecological change, and argues for a reflexive reorientation of spatial planning. Only by critically examining its own role between stabilization and transformation can spatial planning become an active agent of change.
Keywords: Spatial planning; Transformation; Sustainability; Exnovation; Unlearning; Reflexivity